Antimicrobial efficacy of TiO₂ against foodborne pathogens in microgreen systems - Abou Elias, Chiara Lynn (My University, 2024)
Microgreens are superfoods that have grown in popularity due to their high nutritional content. Recent recalls have highlighted several food quality and safety concerns since microgreens are harvested shortly after germination in a warm and moist environment. Titanium dioxide (TiO₂) has been used to inactivate microorganisms through the photocatalytic generation of reactive oxygen species. This technology is stable, non-toxic, inexpensive, and operates under ambient conditions. Hence, this study aimed to (1) Evaluate the efficacy of TiO₂ as a potential antimicrobial agent for water disinfection against E. coli and Listeria in a controlled laboratory setting; and (2) Verify the effect of TiO₂ on the growth of experimentally inoculated microgreens on a soilless substrate by evaluating microbial reduction and chemical-physical parameters. TiO₂ antimicrobial activity was tested against E. coli and Listeria at 0.1% w/v for up to 4 hours in vitro conditions. At appropriate time intervals, the bacterial population was enumerated. The experiments were performed in triplicate, with statistical significance set at a P value < 0.05. Both E. coli and Listeria populations exhibited significant reductions (P < 0.05) with log CFU/mL reductions of 3.59 and 4.66, respectively. The best conditions for microbial reduction were used in the microgreen growing systems where arugula seeds or mats were experimentally inoculated with E. coli and Listeria. Germination and growth were monitored for 14 days, and bacterial count, color, pH, height, weight, and titratable acidity were evaluated. Two tower systems were run in parallel: a control where no TiO₂ was applied, and a treatment where 0.05% w/v TiO₂ was integrated into the water reservoir system. Experiments were conducted in triplicate with statistical significance set at a P value < 0.05. By the end of the experiment, Listeria populations were reduced by 2.17 log CFU/cm² in samples grown from contaminated mats and by 1.91 log CFU/cm² in seed-contaminated samples, both showing statistically significant reductions as compared to the control (P < 0.05). E. coli populations were significantly reduced only in the seed-inoculated samples treated with TiO₂ with a 1.57 log CFU/cm² reduction as compared to the control (P = 0.05). These results suggest that both contamination routes pose a potential risk in microgreens as pathogens can survive. No significant differences (P > 0.05) were observed in the pH, height, weight, or the a* and L* color values. There was a significant difference in titratable acidity between control and mat-inoculated samples with L. innocua and the b* color value between control and mat-inoculated samples with L. innocua and E. coli (P < 0.05). This study provides insight into the potential efficacy of TiO₂ to reduce the risk of foodborne pathogens in microgreen systems.
Keywords: Titanium dioxide; Antimicrobial; Microgreens; Pathogen reduction; Food safety; Microgreen system